Quality Analysis of Different Varieties of Potato Snowflakes Powder - Yuqing HUI; Huifang SHEN; Xinmiao YAO; Ye ZHOU; Qingquan LI; Qingshen SUN (Shipin gongye ke-ji, 2023)
In this study, 11 varieties of potatoes were selected as raw materials to process whole powder under the same conditions. The quality differences of snowflake whole powder prepared by different varieties of potatoes were studied by measuring components, iodine blue value, chroma, water holding capacity (WHC), oil holding capacity (OHC), freeze-thaw stability and other indicators, so as to clarify the influence of different varieties of potatoes on the quality of whole powder. The results showed that the Longshu 6 had the strongest WHC (9.84 g/g), OHC (1.63 g/g) and coagulation capacity, and the attenuation value (315.2 RVU) was significantlyhigher than that of the other varieties (P<0.05). Longshu 15 had the highest water content (9.20%). Longshu 9 had the highest viscosity (589.4 RVU) and the strongest shear resistance, but the retrogradation value was 33.9 RVU, with strong gelation and easy aging. Longshu 18 had the highest protein content of 12.29 g/100 g, but less starch content (46.24 g/100 g), the highest water absorption rate (0.55%) and the worst freezing resistance, so it is not suitable for processing products that need to be frozen and stored. The reducing sugar content of Atlantic (0.24 g/100 g) was significantly lower than that of other varieties (P<0.05), the iodine blue value (26.28) was the highest, and the free starch content was the highest. Longshu 15 had the largest L* value (91.49) and smaller b* value (14.96), with bright colors and a more marketable appearance. This study would provide data support for the selection of dominant potato varieties for the development of potato whole powder by comparing the relationship between potato quality and varieties.